Effects of upper body anthropometrics and handgrip strength on ball velocity in female handball players - Canli, U.; Kurt, C.; Atalag, O. (Turkish Journal of Sport and Exercise, 2021)
The aim of this study is to analyze the relationship between ball velocity thrown from two different positions, parameters of upper body anthropometrics and hand grip strength as a marker of upper body strength. Twelve well-trained female handball players (age, 22.47±4.57 years; body mass, 66.70±11.05 kg; height, 167.33±7.41 cm; handball experience, 9.91±3.47 years), playing in a team that competes in the first division of the Handball League of Turkey joined this study. Body weight, height, body mass index (BMI), body fat percent and trunk muscle mass, hand length and breadth, sitting height, arm span index and dominant hand grip strength measured by using a stadiometer, bioelectric impedance device, anthropometric set, fiberglass measuring tape and hand grip dynamometer respectively. Ball velocity was measured with a speed radar for both throwing positions (throws are made from a sitting position either with a non-throwing hand on the floor (RP) or non-throwing arm free (RS). According to hierarchical multiple regression analysis carried out; the original contribution of fat percentage, trunk muscle mass, BMI and handgrip strength included in the model in the first step is not significant within the model and both RP and RS were not able to predict ball velocity (p>0.05). It was also determined that hand length, hand breadth, sitting height and arm span index which were included in the model in the second step were not significant and did not predict the ball velocity for both RP and RS as well (p>0.05). However, there was a positive relationship between trunk muscle mass and ball velocity with RP (r = 0.831; p<0.05). No relationship was found between other variables and ball velocity for both RP and RS. According to the results of the study, handball players and their coaches might consider designing resistance training programs that put an emphasis on increasing trunk muscle mass to increase the ball velocity during over arm throws.